2018
DOI: 10.1053/j.gastro.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Determining Risk of Colorectal Cancer and Starting Age of Screening Based on Lifestyle, Environmental, and Genetic Factors

Abstract: We used data from 2 large international consortia to develop CRC risk calculation models that included genetic and environmental factors along with family history. These determine risk of CRC and starting ages for screening with greater accuracy than the family history only model, which is based on the current screening guideline. These scoring systems might serve as a first step toward developing individualized CRC prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
228
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 243 publications
(248 citation statements)
references
References 95 publications
16
228
2
2
Order By: Relevance
“…The prediction from the joint score increased the AUC to 0.636. This AUC estimate is similar to AUCs reported from comprehensive large case–control and cohort studies on CRC risk, which combined environmental risk factors and SNPs, such as the Spanish population study with 21 SNPs and AUC = 0.63 and the study on multiple populations with 63 SNPs and AUC = 0.63 …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The prediction from the joint score increased the AUC to 0.636. This AUC estimate is similar to AUCs reported from comprehensive large case–control and cohort studies on CRC risk, which combined environmental risk factors and SNPs, such as the Spanish population study with 21 SNPs and AUC = 0.63 and the study on multiple populations with 63 SNPs and AUC = 0.63 …”
Section: Discussionsupporting
confidence: 84%
“…This is in agreement with expectations, as the predictive performance of risk scores tested in independent and external samples is generally lower than in the sample used for model development. The prediction from the single GRS (AUC = 0.606) is within the range reported from large case–control studies on CRC risk, while using different set and number of SNPs (e.g., study on multiple populations mainly of north European descent, 10 SNPs, AUC = 0.57; multiple populations of European descent, 27 SNPs, AUC = 0.60; Spanish population, 21 SNPs, AUC = 0.56; multiple populations, 63 SNPs, AUC = 0.60). The prediction from the joint score increased the AUC to 0.636.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have shown that CRC is caused by environmental factors (e.g., diet and lifestyle) as well as genetic factors, which may play an essential role in CRC risk . Reliable screening measures are needed to diagnose CRC early; therefore, a genetic risk assessment tool to identify individuals at high risk for developing CRC is needed …”
Section: Introductionmentioning
confidence: 99%
“…Several previous genome‐wide association studies (GWASs) have identified single nucleotide polymorphisms (SNPs) associated with CRC risk . However, few studies have explored the value of these SNPs in evaluating an individual's risk of CRC, particularly in Chinese populations . Therefore, we systematically analyzed 85 GWAS‐identified SNPs (Supporting Information Table S1) using three large‐scale GWAS datasets to determine the potential applications of genetic variants (Supporting Information Table S2).…”
Section: Introductionmentioning
confidence: 99%